2014
DOI: 10.1007/s00423-014-1160-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for primary gastrointestinal stromal tumours: are they the same in the multidisciplinary treatment era?

Abstract: In the multidisciplinary management of GIST, serosal perforation may represent an additional predictor of recurrence along with mitotic rate. Complete macroscopic surgical resection is the most reliable prognostic factor, and an aggressive surgical approach should be advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Consistently, studies by McCarter et al and Cananzi et al showed no significant difference in RFS in GIST undergoing R0 and R1 resection. 38,39 In 2012, the European Society for Medical Oncology (ESMO) guideline deleted microscopic margins as a prognostic factor for GISTs. 40,41 These results suggested that R0/R1 may not be associated with GIST recurrence and may not be suitable for SMT evaluation because the tumor is often enucleated along with the capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, studies by McCarter et al and Cananzi et al showed no significant difference in RFS in GIST undergoing R0 and R1 resection. 38,39 In 2012, the European Society for Medical Oncology (ESMO) guideline deleted microscopic margins as a prognostic factor for GISTs. 40,41 These results suggested that R0/R1 may not be associated with GIST recurrence and may not be suitable for SMT evaluation because the tumor is often enucleated along with the capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 is an important prognostic factor that has been implicated in recurrence and survival and should be included in pathologist’s report[ 118 , 119 ] (See Table 3 ). The depth of tumor infiltration, including serosal penetration has been proposed as a prognostic factor for patients with GISTs with significantly poorer prognosis compared to its absence[ 120 , 121 ].…”
Section: Role Of Pathologistmentioning
confidence: 99%
“…All high-risk patients with detectable ctDNA during surgical treatment displayed a complete response with no detectable tumor-specific ctDNA four weeks following surgery. Although there is a variation of ctDNA shedding intraoperatively among patients with high-risk GIST tumors, all patients with non-radical surgery, known to correlate with poor prognosis (37,38), were ctDNA positive. Our and other data (33) show that tumor-specific mutations that occur as insertions or deletions are more likely to be ctDNA positive.…”
Section: Discussionmentioning
confidence: 91%